An Industrial systems design study on MC Barretto Caloocan Shell Service Station - Camacho, Rowena Grace; Cayanong, Kirby Luke; Malig, Mary Magdalene; Razon, Pocholo (College of Engineering, 2002)
MC Barretto Enterprises is a newly incorporated company supervised by Augustus Caesar Baretto. Its area of business covers Shell Service Stations in Tondo and Caloocan, and a tanker service. This study probed which systems and procedures of MC Barretto affect its internal and external environment. A comprehensive documentation, following a top-to-bottom approach for the study was done in order to analyze all the aspects of the system, from a broad perspective to specific details. Various tools were used in analyzing the strengths and weaknesses of the company, as well as the opportunities and threats they face. Furthermore, the documentation of the system was quantified through a simulation design in order to have a basis for all improvements that the company may undertake. To be able to utilize the company?s inherent strengths and take advantage of the opportunities they have, strategies subdivided according to its planning range were formulated. Implementation plans were given and were reasonably quantified so as to make the benefits visible to the management. The following recommendations were made: (1) adapt a set of ordering system; (2) position several posters displaying various environmental initiatives for customers; (3) make service station accessible to southbound motorists by providing a passageway that would traverse C-3 Road; (4) carry out intensive advertising through a set of marketing campaign (6) put-up a Hen Lin franchise beside the lube area; and (7) integrate a motor shop. The importance of Sustainable Development is emphasized in this study. Alternatives were analyzed in the hope of minimizing, if not avoid, the harmful effects that the company?s operations may cause to the environment. In the completion of the study, it was deemed that all the set objectives were attained; it has served much greater purpose in providing the researchers invaluable experience in the whole industrial design systems process. Especially in the training that the whole project has given in the documentation and analysis of a comprehensive systems approach.